Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pntd.0009316
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced passive surveillance dengue infection among febrile children: Prevalence, co-infections and associated factors in Cameroon

Abstract: Dengue virus (DENV) causes a spectrum of diseases ranging from asymptomatic, mild febrile to a life-threatening illness: dengue hemorrhagic fever. The main clinical symptom of dengue is fever, similar to that of malaria. The prevalence of dengue virus infection, alone or in association with other endemic infectious diseases in children in Cameroon is unknown. The aim of this study was to determine the prevalence of dengue, malaria and HIV in children presenting with fever and associated risk factors. Dengue ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
1
17
0
1
Order By: Relevance
“…Previous research has mostly focused on disease control and prevention mechanism ( Gao and Yu, 2020 ; Kang et al, 2020 ). The first set of research considered the epidemiology of infections ( Nkenfou et al, 2021 ; Shah et al, 2020 ). The second set of research determined the effect of various factors on epidemic prevention ( Ahmad et al, 2021 ; Yang and Ren, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mostly focused on disease control and prevention mechanism ( Gao and Yu, 2020 ; Kang et al, 2020 ). The first set of research considered the epidemiology of infections ( Nkenfou et al, 2021 ; Shah et al, 2020 ). The second set of research determined the effect of various factors on epidemic prevention ( Ahmad et al, 2021 ; Yang and Ren, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this study is related to the elimination of malaria-positive cases before arbovirus screening. Two studies reported cases of DENV/malaria co-infected children in Yaoundé, Cameroon [31,32]. Moreover, several studies around the world described cases of DENV/malaria, malaria/DENV/CHIKV and malaria/CHIKV co-infections [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Denguemalaria coinfection was firstly documented in children attending healths centers in Yaoundé [15]. Later, Nkengfou et al found a coinfection rate of 19.5% in infants consulting at the Centre Mère-Enfant in Yaounde [10]. In another study, a malaria-dengue coinfection rate of 13% was documented in the New-Bell district in Douala [14].…”
Section: Introductionmentioning
confidence: 98%
“…The copyright holder for this this version posted September 10, 2021. ; https://doi.org/10.1101/2021.09.03.21263073 doi: medRxiv preprint Mère-Enfant in Yaounde [10]. In another study, a malaria-dengue coinfection rate of 13% was documented in the New-Bell district in Douala [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation